Dietary inequality in adolescents: a review of scientific literature - Rivera-Navarro, Jesús (Acciones e Investigaciones Sociales, 2021)
This article is based on an analysis of the scientific literature on dietary inequality among the adolescent population. This analysis shows that, in Spain, diseases related to unhealthy eating are increasing at the same time as the Mediterranean diet is being replaced by another type of diet in which processed foods predominate. One of the most vulnerable groups with regard to unhealthy eating is adolescents. They have a worse diet than other age groups, but among themselves, there are also differences according to socio-economic status. The environment where people live can be a good indicator to analyse the above-mentioned differences, thus, the neighbourhood where people live seems to be a determining factor in their health and also in their diet. There are two theoretical models, which we believe are suitable for the study of dietary differences in adolescents; one is the model of dietary determinants, composed of the cultural, physical, social and personal environment; the other model is the Angelo framework, based mainly on obesity and including factors related to both diet and physical activity.
Keywords: Food, inequality, neighbourhood, adolescents